Penerapan Pendekatan Cooperative Learning Tipe Jigsaw dalam Upaya Meningkatkan Aktivitas dan Hasil Belajar Peserta Didik Kelas I SD Negeri 27 Ampenan - Fajuri Fajuri (Universitas Pendidikan Mandalika, 2019)
This study aims to determine the effectiveness of the application of the Jigsaw cooperative learning approach in an effort to improve the activities and learning outcomes of grade 1 students at SD Negeri 27 Ampenan. The benefits of this research are to improve teacher competence in the learning process and to increase student learning activities and outcomes. This research was conducted using a classroom action research method conducted in class I 27 Ampenan Elementary School Semester Two Academic Year 2017/2018, with a total of 37 students. The final results of the action in the second cycle showed that the results of teacher observation obtained an average score (4.57) and the results of student observations achieved an average score (4.51). While student learning outcomes are achieving an average value (82.51), meaning that the indicators of success (> 75.00) have been exceeded. Because the indicators of success have been proven, the research was declared successful and stopped in the second cycle.